THE EFFECTIVENESS OF SECONDARY METABOLIC BIOINSECTICIDES OF METARHIZUM MUSHROOMS ON CORN GROWER PESTS Spodoptera frugiperda J.E SMITH (Lepidoptera: Noctuidae). - Apri Silia M. Dampi; Jackson Watung; Sofia Wantasen (Sam Ratulangi University, 2022)
This study aims to determine the effectiveness of the use of bioinsecticide secondary metabolites of the fungus Metarhizium on corn plants against S. frugiperda larvae. The results of the study are expected to provide benefits for farmers in controlling S. frugiperda pests with secondary metabolites of the fungus Metarhizium on corn plants. This research was conducted at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Sam Ratulangi University, Manado, North Sulawesi. The study lasted for 3 (three) months from February to April 2021. This study used a completely randomized design (CRD) with 4 treatments, namely MS0 (control), MS1 (secondary metabolite concentration 10 cc/1ltr), MS2 (secondary metabolite). The concentration of 20 cc/1ltr), MS3 (secondary metabolite concentration of 30 cc/1ltr), and repeated 5 times. The number of pests per jar is 1 with a total of 80 pests. The results showed that the most effective concentration of secondary metabolites of the fungus Metarhizium in killing S. frugiperda larvae was found at a concentration of 30cc/ltr of water with a mortality of 95%. Then followed by treatment with a concentration of 20cc/ltr of water with a mortality of 75% and a concentration of 10cc/ltr of water with 45%. Keywords: Effectiveness, secondary metabolites Metarhizium of fungus, S. frugiperda, Manado.AbstrakPenelitian ini bertujuan untuk mengetahui efektifitas dari penggunaan bioinsektisida metabolit sekunder jamur Metarhizium pada tanaman jagung terhadap larva S. frugiperda. Hasil penelitian diharapkan dapat memberi manfaat bagi para petani dalam pengendalian hama S. frugiperda dengan metabolit sekunder jamur Metarhizium pada tanaman jagung. Penelitian ini dilaksanakan di Laboratorium Hama dan penyakit Tumbuhan Fakultas Pertanian Universitas Sam Ratulangi Manado Sulawesi Utara. Penelitian berlangsung selama 3 ( tiga ) bulan yakni sejak bulan Februari sampai dengan April 2021. Penelitian ini menggunakan Rancangan Acak Lengkap ( RAL ) dengan 4 perlakuan yaitu MS0 (Kontrol), MS1 (Metabolit sekunder konsentrasi 10 cc/1ltr), MS2 (Metabolit sekunder konsentrasi 20 cc/1ltr), MS3 (Metabolit sekunder konsentrasi 30 cc/1ltr), dan diulang 5 kali. Jumlah hama per toples 1 ekor dengan jumlah hama seluruhnya 80 ekor. Hasil penelitian menunjukan bahwa konsentrasi metabolit sekunder jamur Metarhizium yang paling efektif membunuh larva S.frugiperda terdapat pada konsentrasi 30cc/ltr air dengan mortalitas sebesar 95%. Kemudian diikuti oleh perlakuan konsentrasi 20cc/ltr air dengan mortalitas sebesar 75% dan konsentrasi 10cc/ltr air sebesar 45%. Kata Kunci : Efektivitas, metabolit sekunder jamur Metarhizium, S.frugiperda,